Measurement of Public Satisfaction Level with The Mahameru Walk Thru (Mawatu) Service at The Joint Samsat Office of West Surabaya City, Surabaya - Zahrani Putri Anggraeni; Meirinawati M; Trenda Aktiva Oktariyanda; Deby Febriyan Epriliant (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Quality public services are one of the important factors in improving public satisfaction. Often encountered in the implementation of public services, there are many stages that must be passed. The West Surabaya Samsat Joint Office, as the administrator of motor vehicle tax services, has introduced an innovative service called Mahameru Walk Thru (Mawatu) to provide convenience, speed, and comfort for the public. This study aims to measure the level of public satisfaction with the Mahameru Walk Thru service at the Surabaya West Joint Samsat Office in Surabaya City according to Hidayat (2019) with 7 indicators: work values, honesty, responsibility, dedication and commitment to serve, work motivation, mastery of communication skills, and mastery of technology. The method used in this study is a descriptive quantitative research method involving 100 respondents from the taxpayer community in the Mawatu service. The results show that the level of public satisfaction with the Mahameru Walk Thru service at the Surabaya Barat Samsat Joint Office is in the very high category, with an average score of 4.36. Work values had the highest score of 4.46, while responsibility had the lowest score of 4.22. All satisfaction indicators received positive ratings from respondents, indicating that the services provided met the expectations of the community.